AKURASI PENGGUNAAN METODE PANJANG KALI LEBAR UNTUK PENGUKURAN LUAS DAUN JAGUNG (Zea mays L.) DAN KEDELAI (Glycine max L.) - Usman .; Syahrudin .; Kambang Vetrani Asie; Suparno . (Jurusan Agroekoteknologi Fakultas Pertanian Untirta, 2018)
The purpose of this study was to determine the accuracy of the method of long width method for measurement of corn leaf area (Zea mays L.) and soybean (Glycine max L) compared to method of leaf area meter. This study use designed by comparing the two methods, then the statistical test was done with the t-test. The result of this study showeed that correction factor (k) of leaf area length method obtained with Agustina (1988) version is not significantly different from Sitompul and Guritno version (1995). The k values used in the calculation of the leaf area with the long-width method of Sitompul & Guritno's (1995) version can be used at any age of observation on both corn and soybean crops, for Agustina (1988) the k value on corn leaves can be used every age of observation, but in soybean crop needs to be made a new k value at the age of the plant further (eg 5 MST) with the number of leaves more. The accuracy of the long-width method for measuring leaf area in maize compared with LAM method is quite high, Sitompul & Guritno (1995) version reaches 100% and Agustina's version is slightly lower that is 75%. The accuracy of Sitompul & Guritno (1995) and Agustina (1988) long-range method for measuring leaf area on soybean crops compared with very low LAM method is 25%. The accuracy of the method of length method times compared to LAM method toward measurement of corn leaf area is higher than in soybean crop Keywords: Leaf area, of corn and soybean leaf, Length method times width, Leaves